OOPS: The Ontology of Plant Stress: A semi-automated standardization methodology - Meier A.; Laporte, Marie-Angélique; Elser J.; Cooper L.; Preece, J.; Jaiswal, P.; Poolen, J. (2018)
Plant stress traits are important breeding targets for all crop species. Massive amounts of research dollars are spent generating data to combat plant diseases and environmental stress. Often this data is used to achieve a single goal, and then left in a repository to never be used again. As a scientific community, we should be striving to make all publicly funded data reusable, and interoperable. This goal is achievable only through careful annotation using universal data and metadata standards. One such standard is the use of a standardized vocabulary, or ontology. This paper presents a semi-automated method to define and label plant stresses using a combination of web scraping and ontology design patterns. Standardizing the definitions and linking plant stress with established hierarchies leverages previous work of developed knowledge bases such as taxonomic classifications and other ontologies.